2000
DOI: 10.1139/cjb-78-3-305
|View full text |Cite
|
Sign up to set email alerts
|

Foliar plasticity of hybrid spruce in relation to crown position and stand age

Abstract: This study examined the foliar response of putative hybrid Engelmann × white × Sitka spruce (Picea engelmannii Parry × Picea glauca (Moench) Voss × Picea sitchensis (Bong.) Carr) needles in relation to crown position and across three stages of development (15, 55, and 145 years). We focused on the morphological and anatomical response, and used physiological measures (photosynthesis and stomatal conductance) to emphasize the important relationship between structure and function. We found that needles from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 44 publications
8
35
0
6
Order By: Relevance
“…Plants growing under strong light have well developed palisade parenchyma, thicker leaves, relatively larger leaf area, higher biomass, increased photosynthesis, and lower contents of chlorophyll, carotenoid, and nitrogen (Je et al, 2006;Yang et al, 2007;Huang et al, 2008;Volkova et al, 2010). Structural characteristics of conifer needles are often strongly related to gradients in long-term light availability within canopies and across stands (Richardson et al, 2000;Richardson et al, 2001;Niinemets et al, 2002;Lhotáková et al, 2007;Niinemets et al, 2007). The lower NBRCC and NBRCW values and higher CCH/ NH proportion in peat bog populations and populations growing on rocky substrates can be explained as a response to increasing environmental stress, which is accompanied by a decline in photosynthetic and growth rate, since higher leaf age compensates for low photosynthesis (Schoettle et al, 1994;Reich et al, 1995).…”
Section: Differentiation By Habitat Typementioning
confidence: 99%
“…Plants growing under strong light have well developed palisade parenchyma, thicker leaves, relatively larger leaf area, higher biomass, increased photosynthesis, and lower contents of chlorophyll, carotenoid, and nitrogen (Je et al, 2006;Yang et al, 2007;Huang et al, 2008;Volkova et al, 2010). Structural characteristics of conifer needles are often strongly related to gradients in long-term light availability within canopies and across stands (Richardson et al, 2000;Richardson et al, 2001;Niinemets et al, 2002;Lhotáková et al, 2007;Niinemets et al, 2007). The lower NBRCC and NBRCW values and higher CCH/ NH proportion in peat bog populations and populations growing on rocky substrates can be explained as a response to increasing environmental stress, which is accompanied by a decline in photosynthetic and growth rate, since higher leaf age compensates for low photosynthesis (Schoettle et al, 1994;Reich et al, 1995).…”
Section: Differentiation By Habitat Typementioning
confidence: 99%
“…Sample trees were selected from three fire-origin stands with approximate ages of 20 years (S20), 60 years (S60) and 140 years (S140). The stands were chosen previously for a related study [34]. The two older stands (S60 and S140) were located within the Date Creek research area managed by the British Columbia Ministry of Forests while the youngest stand (S20) was in an adjacent wildfire known locally as the Ken Fire.…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies have shown that in old conifer trees the duration of wood formation is shorter than in younger ones [28]. It is well-known that tree ageing affects carbon allocation to different parts of the plant, reduces the foliar efficiency and gas attributes [29,30]. Thus, decline of photosynthetic rate in old conifer species induce the increasing of climatic sensitivity, especially towards temperatures [31].…”
Section: Discussionmentioning
confidence: 99%